A quantum-inspired, biomimetic, and fractal framework for self-healing AI code generation: bridging responsible automation and emergent intelligence - Nehzati, Mohammadreza (Frontiers in Artificial Intelligence, 2025)
AI-powered code generation systems available today are ill-suited for deployment in agile software development contexts due to various limitations. The paper proposes a self-healing counterpart framework based on quantum-inspired optimization, biomimetic, and fractal principles to solve these fundamental issues. Our Quantum Solution Space Manager keeps more than one candidate solution in superposition states. In doing so, it achieves 94.7% code correctness (versus 87.3%) with respect to a leading approach. The biomimetic error detection system, inspired by biological immune mechanisms, has a sensitivity of 95.2 per cent, with a false-positive rate of 2.3 per cent. Effectively, 94.7 per cent of detected errors are automatically corrected. Fractal optimization allows for a considerable 89.4% success rate during cross-architectural propagation, while distributed intelligence networks allow different intelligences and agents to learn together. The framework is validated as effective through an analysis of 15,000 software engineering tasks across five domains. This helps reduce the critical error rate by 54% and the remaining development time by 41%, along with notable improvements in maintainability and security metrics. The results lay down the path for adaptive software development systems to create responsible automation and emergent intelligence.